162k views
5 votes
Simplify the expression given below.

Simplify the expression given below.-example-1

1 Answer

7 votes

Answer:

Option B.
(1)/(3x+1).

Explanation:

The given expression is
(x+2)/(x^(3)+2x^(2)-9x-18)/ (3x+1)/(x^(2)-9)

In this expression we will simplify
(x+2)/(x^(3)+2x^(2)-9x-18) first.

=
(x+2)/(x^(2)(x+2)-9(x+2))


=(x+2)/((x+2)(x^(2)-9))


=(1)/(x^(2)-9)

Now we can rewrite the given expression as


=(1)/(x^(2)-9)/ (3x+1)/(x^(2)-9)


=(1)/(x^(2)-9)* (x^(2)-9)/(3x+1)


= (1)/(3x+1)

So option B.
(1)/(3x+1) is the right answer.


User Amir Afghani
by
5.3k points